PRESSURE INJURIES AND ASSOCIATED FACTORS AMONG PATIENTS TREATED IN THE INTENSIVE CARE AND TOXICOLOGY DEPARTMENT AT DUC GIANG GENERAL HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the characteristics of pressure ulcers and associated factors among patients treated in the Intensive Care and Toxicology Department at Duc Giang General Hospital in 2025.Subjects and methods: A cross-sectional descriptive study was conducted, including all inpatients treated at Duc Giang General Hospital, from March 2025 to June 2025.Results: The mean age of the patients was 70.5 ± 17.8 years; 63.5% were female. The proportion of patients with a length of hospital stay > 7 days was 75.5%, and 62.5% required mechanical ventilation. The incidence of newly developed pressure ulcers was 14%. The most common anatomical sites were the buttocks (40.6%) and the sacral region (31.3%). Several factors were significantly associated with the occurrence of pressure ulcers, including age ≥ 80 years (OR = 2.489; p = 0.024), mechanical ventilation (OR = 3.157; p = 0.021), and length of hospital stay > 7 days (OR = 4.888; p = 0.021).Conclusion: A total of 14% of patients treated in the Intensive Care and Toxicology Department at Duc Giang General Hospital developed new pressure ulcers during hospitalization. Most pressure ulcers were classified as stage I and II. Factors such as advanced age, mechanical ventilation, and prolonged length of hospital stay were associated with an increased risk of pressure ulcer development. Early preventive interventions should therefore be implemented, particularly for patients at high risk.
Keywords: Pressure ulcers, Braden ulcer risk assessment scale, Duc Giang General Hospital.